Rheology of vacuum-concentrated kalamansi juice and sugar-concentrated juice mixed with hydrocolloid - Ocasla, Joebit C.
The rheological behavior of vacuum-concentrated kalamansi juice and sugar concentrated juice containing hydrocolloid was determined using an RVT rotational viscometer at rotational speeds of 5, 10, 20, 50, and 100 rev min -1. The vacuumconcentrated juice has total soluble solids of 50, 55, and 60 ˚Brix while the juice with hydrocolloid has xanthan gum concentrations of 0.2, 0.3, and 0.4 % (w/w). The speed and torque (0-100% on the scale) readings obtained from rotational viscometer with disc-type spindles were converted into viscosity functions to yield power law constants and shear rate- shear stress data. The analysis of the log shear stress - log speed dependence by linear regression indicated that this conversion was satisfactory (in all cases, with correlation coefficient r2> 0.9512). The power law and Herschel-Bulkley model were employed in the process to determine the consistency index and flow behavior index.